Analysis of the english as a foreign language speaking development in rural environment - Ortiz Minda, Kendra Anahí (2024)
This research work examines the speech development of students at the 'Unidad Educativa Rumipamba,' focusing on identifying areas of weakness and suggesting useful activities to enhance oral expression skills in the English language. The significance of this research stems from the need to strengthen students' communication skills, particularly in rural areas where access to educational resources is limited for example: speakers, books, projector, internet, didactic cards\; also, the opportunities to interact with the English language may be limited outside of the classroom. According to the gathered information from different websites, theses and research works the lack of resources and the shortage of English teachers make rural school students have limitations to improve their oral development. These difficulties hamper students' academic and career prospects by contributing to noticeable shortcomings in their English language competence. The main objective of this study is to analyze the gaps in oral English language competence in rural school students, and suggest some activities that help them to develop their English skills, offering practical suggestions to improve their linguistic competence and confidence in speaking through everyday contexts tasks, acquiring an understanding of the unique needs and challenges they face. This research carried out a mixed approach, combining both qualitative and quantitative methods. Data collection involves the use of survey with questions addressed to teachers and observation sheets to gather comprehensive information about the students' current levels of competence, and their performance in the classroom considering the participation of students during English classes.